Meu mar - Bucuane, Juvenal (Editora do Carmo, 2018)
OCLC: 1153344051
Keywords: digte

Meu mar - Bucuane, Juvenal (Cavalo do Mar, 2019)
OCLC: 1119388919
Keywords: 2000-2099; 21st century; Mozambican poetry (Portuguese); Mozambique; Poetry; Poésie; poetry; poetry (form)

Crendice ou crença: quando os manes ancestrais se tornam deuses - Bucuane, Juvenal (Alcance, 2012)
A novel
OCLC: 863635474

Arresto de vozes: ou o cúmulo discursivo literário - Bucuane, Juvenal (Alcance, 2017)
OCLC: 1003193063
Keywords: African literature (Portuguese); African literature (Portuguese) Black authors History and criticism; Authors; Mozambican; Authors; Mozambican Criticism and interpretation; Black authors History and criticism; Bucuane; Juvenal; 1951- Criticism and interpretation; Criticism and interpretation; Criticism; interpretation; etc; Essais; Essay; Essays; History and criticism; Intellectual life; Littérature africaine (portugaise) Auteurs noirs Histoire et critique; Littérature mozambicaine (portugaise) Histoire et critique; Mozambican literature (Portuguese); Mozambican literature (Portuguese) History and criticism; Mozambique; Mozambique Intellectual life; essays; Écrivains mozambicains Critique et interprétation

Meu mar - Bucuane, Juvenal (Cavalo do Mar, 2018)

O fundo pardo das coisas: poesia - Bucuane, Juvenal; Cuna, Aurélio (Alcance, 2014)
OCLC: 951170987
Keywords: Anthologie; Lyrik; Mozambican poetry (Portuguese); Moçambique; Poetry; Portugiesisch; Poésie; poetry

Detalhes de uma vida de silêncio - Baptista Júnior, Heliodoro; Bucuane, Juvenal (Oleba, 2017)